Impact of Referring on Survival of Patients with Head and Neck Cancer Treated in Khon Kaen Hospital, Thailand - Mongkolthawornchai, Khasaya; Vatanasapt, Patravoot (Srinagarind Medical Journal, 2024)
Background and Objective: Because of the limited treatment facilities in the primary hospital, most head and neck cancer (HNC) patients had to be referred to higher centers lead to long waiting time. The aim of this study was to compare the survival of patients with HNC treated at Khon Kaen Hospital, between those who resided in Khon Kaen and those who were referred from outside. Methods: A retrospective cohort study was conducted. The data of HNC patients treated at Khon Kaen Hospital between 2012 and 2017 were obtained from a hospital-based cancer registry. Survival analysis was performed to compare the patients residing in Khon Kaen province with those referred from outside. Results: A total of 927 cases were retrieved, with age between 40 and 80 years, 60% were male. Cancer of oral cavity was the most common site (38.2%), followed by nasopharynx (30.9%), larynx and hypopharynx combined (14.4%) and oropharynx (9.9%). More than half of the patients resided in Khon Kaen province (57.9%). For early-stage cancer, median survival time was significantly better in the residence group than in the referring group (7.21 and 3.96 years, respectively). Likewise, in the advanced stage, median survival time and observed survivals were not significantly different. Conclusions: Referring of early-stage HNC cases results in a poorer survival for patients compared with those treated within the area of their residences. Therefore, the ability to treat at least an early-stage HNC should be improved in provincial hospital.